Fine-Mapping of 18q21.1 Locus Identifies Single Nucleotide Polymorphisms Associated with Nonsyndromic Cleft Lip with or without Cleft Palate - Mitra, Amit K.; Stessman, Holly A. F.; Schaefer, Robert J.; Wang, Wen; Myers, Chad L.; Van Ness, Brian G.; Beiraghi, Soraya (Frontiers in Genetics, 2016)
Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common congenital birth defects. NSCL/P is a complex multifactorial disease caused by interactions between multiple environmental and genetic factors. However, the causal single nucleotide polymorphism (SNP) signature profile underlying the risk of familial NSCL/P still remains unknown. We previously reported a 5.7-Mb genomic region on chromosome 18q21.1 locus that potentially contributes to autosomal dominant, low-penetrance inheritance of NSCL/P. In the current study, we performed exome sequencing on 12 familial genomes (6 affected individuals, 2 obligate carriers, and 4 seemingly unaffected individuals) of a six-generation family to identify candidate SNPs associated with NSCL/P risk. Subsequently, targeted bidirectional DNA re-sequencing of polymerase chain reaction (PCR)-amplified high-risk regions of MYO5B gene and sequenom iPLEX genotpying of 29 candidate SNPs were performed on a larger set of 33 members of this NSCL/P family (10 affected + 4 obligate carriers + 19 unaffected relatives) to find SNPs significantly associated with NSCL/P trait. SNP versus NSCL/P association analysis showed the MYO5B SNP rs183559995 GA genotype had an odds ratio of 18.09 (95% Confidence Interval=1.86-176.34; gender-adjusted Pvalue=0.0019) compared to the reference GG genotype. Additionally, the following SNPs were also found significantly associated with NSCL/P risk: rs1450425 (LOXHD1), rs6507992 (SKA1), rs78950893 (SMAD7), rs8097060, rs17713847 (SCARNA17), rs6507872 (CTIF), rs8091995 (CTIF) and rs17715416 (MYO5B). We could thus identify mutations in several genes as key candidate SNPs associated with the risk of NSCL/P in this large multi-generation family.